Formação continuada em serviço: do coordenador pedagógico ao professor o caso da rede municipal de São Paulo - Souza, Ligia Ramo de (2017)
The quality of teacher training has been a recurring question, both for newly trained professionals and those who have been teaching for some time. For this intervening research, such questioning is pertinent. The Municipal Department of Education (SME) of São Paulo, in compliance with regulatory frameworks, enables ongoing training in service to teachers, in the school itself, mediated by a pedagogical coordinator. This research will focus on the challenges of this training, verifying the referrals of the pedagogical coordinator through this assignment, within schools of the Municipal network of São Paulo. The scope of the research is to investigate how this formation occurs, noting how those involved in the process find ways or ways, contributions or not contributions to their desires, taking into account the daily necessities of the school and focusing on learning the Students. In addition to the bibliographical survey on the subject, the research draws on volunteer testimonies of pedagogical coordinators, thanks to which the collective records of formation are mapped throughout 2016. In order to discuss the instruments of action for training, this intervention research is configured , Whose proposal materializes in the tessitura of constructions for such moments.